SPECTRAL AND POLARIMETRIC STUDY OF CLOSE BINARY SYSTEMS XZ CEP AND V 448 CYG WITH A COMPOSITE SPECTRUM - Glazunova, L. V.; Manilova, G. V. (Одеські астрономічні публікації, 2017)
The main parameters of the close binaries V448 Cyg and XZ Cep were determined. Computation of the chemical composition of the atmospheres of their primary components showed the existence of the hydrogen deficiency in them. The polarimetric measurements allowed to establish the sparse structure of the circumstellar envelopes.